Macroalgae-Inspired Brominated Chalcones as Cosmetic Ingredients with the Potential to Target Skin Inflammaging - Ana Jesus; Sara Gimondi; Sónia A. Pinho; Helena Ferreira; Nuno M. Neves; Andreia Palmeira; Emília Sousa; Isabel F. Almeida; Maria T. Cruz; Honorina Cidade (Marine Drugs, 2025)
Skin aging is mainly caused by external factors like sunlight, which triggers oxidative stress and chronic inflammation. Natural halogenated flavonoids have demonstrated anti-inflammatory properties. Inspired by the macroalgae-derived bromophenol BDDE, we investigated the anti-inflammatory potential of structure-related chalcones (1–7). Chalcones 1 and 7 showed the least cytotoxicity in keratinocyte and macrophage cells. Chalcones 1, 2, 4, and 5 exhibited the most significant anti-inflammatory effects in murine macrophages after lipopolysaccharide stimulation, with chalcone 1 having the lowest IC50 value (≈0.58 μM). A SNAP assay confirmed that chalcones do not exert their effects through direct NO scavenging. Symmetrical bromine atoms and 3,4-dimethoxy groups on both aromatic rings improved the anti-inflammatory activity, indicating a relevant structure–activity relationship. Chalcones 1 and 2 were selected for study to clarify their mechanisms of action. At a concentration of 7.5 μM, chalcone 2 demonstrated a rapid and effective inhibitory action on the protein levels of inducible nitric oxide synthase (iNOS), while chalcone 1 exhibited a gradual inhibitory action. Moreover, chalcone 1 effectively activated the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway with around a 3.5-fold increase at the end of 24 h at 7.5 μM, highlighting its potential as a modulator of oxidative stress responses. These findings place chalcone 1 as a promising candidate for skincare products targeting inflammation and skin aging.